La scène, l’écran : questionnements identitaires et tensions du désir dans Tom à la ferme de Michel Marc Bouchard et de Xavier Dolan - Stefano Genetti (Itinéraires)
Written in 2010 and first staged in Montreal in 2011, Michel Marc Bouchard’s Tom à la ferme is a highly metatheatrical tragicomedy of homophobia and existential mystification. In 2013, Xavier Dolan’s cinematographic adaptation transforms it into a psychological thriller which explores the fascination with violence and blurs the boundaries between domination and dependence. The playwright and the director having collaborated on the screenplay, the present comparison aims at showing how Bouchard’s play, then Dolan’s film, address the issues of cultural, linguistic and homosexual identity, thereby questioning both the fiction of identity and identity as fiction. This stage-to-screen adaptation involves some slight or substantial modifications as well as a pluralisation of references which, by emphatising the fluctuations and contradictions of desire, problematize the very notion of stable identity.